Eagle minds : selected correspondence of Istvan Anhalt and George Rochberg, 1961-2005 - Anhalt, István; Rochberg, George (CEL - Canadian Publishers Collection., 2007)
Eagle Minds-a selection from the correspondence between the Canadian composer and scholar Istvan Anhalt and his American counterpart George Rochberg-is a splendid chronicle and a penetrating analysis of the swerving socio-cultural movements of a volatile half-century as observed by two highly gifted individuals. Beginning in 1961 and spanning forty-four years, their conversation embraces not only music but other forms of contemporary art, as well as politics, philosophy, religion, and mysticism. The letters chronicle the deepening of their friendship over the years, and the openness, honest.